IL-22RA2 associates with multiple sclerosis and macrophage effector mechanisms in experimental neuroinflammation - Beyeen, Amennai D; Adzemovic, Milena Z; Ockinger, Johan; Stridh, Pernilla; Becanovic, Kristina; Laaksonen, Hannes; Lassmann, Hans; Harris, Robert A; Hillert, Jan; Alfredsson, Lars; Celius, Elisabeth G; Harbo, Hanne F; et al. (The Journal of immunology (1950), 2010)
Multiple sclerosis (MS) is an inflammatory neurodegenerative disease of the CNS. Recent advances in whole-genome screening tools have enabled discovery of several MS risk genes, the majority of which have known immune-related functions. However, disease heterogeneity and low tissue accessibility hinder functional studies of established MS risk genes. For this reason, the MS model experimental autoimmune encephalomyelitis (EAE) is often used to study neuroinflammatory disease mechanisms. In this study, we performed high-resolution linkage analysis in a rat advanced intercross line to identify an EAE-regulating quantitative trait locus, Eae29, on rat chromosome 1. Eae29 alleles from the resistant strain both conferred milder EAE and lower production of proinflammatory molecules in macrophages, as demonstrated by the congenic line, DA.PVG-Eae29 (Dc1P). The soluble IL-22R α2 gene (Il-22ra2) lies within the Eae29 locus, and its expression was reduced in Dc1P, both in activated macrophages and splenocytes from immunized rats. Moreover, a single nucleotide polymorphism located at the end of IL-22RA2 associated with MS risk in a combined Swedish and Norwegian cohort comprising 5019 subjects, displaying an odds ratio of 1.26 (p = 8.0 × 10(-4)). IL-22 and its receptors have been implicated in chronic inflammation, suggesting that IL-22RA2 regulates a central immune pathway. Through a combined approach including genetic and immunological investigation in an animal model and large-scale association studies of MS patients, we establish IL-22RA2 as an MS risk gene.